Differentiated Learning Strategies in Enhancing German Speaking Skills of Class XI Students - Jasinta Putri Mulya Imami; Primardiana Hermilia Wijayati (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
Differentiated learning represents an educational method which adjusts teaching methods according to students' individual learning requirements and their personal interests and their preferred learning approaches. The research implements differentiated learning in German language instruction for speaking skills with class XI-10 students at SMAN 1 Batu while documenting student activities and learning results following this approach. The research used Classroom Action Research (CAR) as its design structure with two learning cycles that included 28 students as participants. The research data collection included observing student behavior and speaking proficiency assessments which were analyzed through qualitative and quantitative descriptive methods. The results demonstrated substantial growth in student speaking abilities because the mastery percentage increased to 89.28% during the second cycle. The students became more active in their learning activities because they used visual, auditory and kinesthetic learning styles. Differentiated learning proves effective for class XI-10 students at SMAN 1 Batu to improve their German speaking abilities while developing their creative communication skills and self-assurance in speaking